Drying method of cleaning part and cleaning system - YAN GUIXIANG (2024)
The invention provides a cleaning part drying method and a cleaning system.The cleaning part drying method is applied to the cleaning system, the cleaning system comprises cleaning equipment and a base, the drying method is executed under the condition that the cleaning equipment is arranged on the base, and the method comprises the steps that in the process of drying treatment on a cleaning part, the cleaning part is dried; the cleaning piece is controlled to rotate multiple times in the first preset direction; wherein in the multiple rotation operations, at least part of the rotation operations meet the following limitation: a time interval exists between two adjacent rotation operations; the rotating paths of the cleaning parts corresponding to the two adjacent rotating operations at least partially do not coincide with each other; in the drying process, the cleaning part is controlled to rotate intermittently, and at least parts of the rotating paths of the cleaning part corresponding to the two adjacent